THE ECONOMIC VALUE OF HYDROLOGICAL SERVICES IN MENDALAM SUB WATERSHED, KAPUAS HULU REGENCY, WEST KALIMANTAN, INDONESIA - Roslinda, Emi; Yuliantini, Yuliantini (Indonesian Journal of Forestry Research, 2014)
Forest ecosystem supports almost all ofÂ  the needs ofÂ  human being through its contribution ofÂ  tangible and intangible values.Â  Currently, the intangible values have gained less attention than the tangible values that causeÂ  underestimation ofÂ  the total value ofÂ  the forest conversion into other more tangibly profitable usages, and miss-management ofÂ  the forest. One ofÂ  the important intangible values is the hydrological value that has been hardly calculated until now.Â  This research the intangible values ofÂ  water for household, transportation, agriculture and fishing in Mendalam Sub Watershed, Kalimantan. The economic values calculated based on market prices, opportunity costs and consumerâs surplus methods. The results showed that based on theÂ Â Â  opportunity cost method the economic values ofÂ  the hydrological services was about Rp 8,043,706,237.50 per year. Meanwhile, the economic values ofÂ  the hydrological services based on the consumerâs surplus method gave lower value than the former method, i.e. Rp 8,031,351,664.60 per year. This study showed that the economic value ofÂ  the hydrological services was very high, which has not been included in the calculation yet. However, without trees there would be no forest and all other values included water value would not exist. Consequently, current forest management should put forest ecosystem as important to consider.